Hydrofuel Generator X for Mini 4 Stroke Engine - Nur Saifullah, Kamarrudin; Md Tasyrif, Abdul Rahman; Ishak, Ibrahim; Muhamad Ikbal, Azudin (Malaysian Invention and Design Society (MINDS), 2010)
Nur Saifullah Kamaruddin and his team won silver at 21st International Invention, Innovation and Technology Exhibition (ITEX) 2010, 14th - 16th May 2010 di Kuala Lumpur Convention Centre (KLCC), Kuala Lumpur, Malaysia.